2020 Cool-Season Forage Variety Recommendations for Florida - A. R. Blount; M. Wallau; E. Rios; J. M. B. Vendramini; J. C. B. Dubeux; Md. A. Babar; K. E. Kenworthy; M. J. Mulvaney; K. H. Quesenberry (EDIS)
Perennial warm-season pasture grasses used in Florida become dormant in late fall and winter because of short days, cooler temperatures, and frosts. Many livestock producers may choose to establish cool-season annual pasture species to supplement their forage production. These plants are usually higher in total digestible nutrients (TDN) and crude protein (CP) than summer perennial grasses, translating into greater animal performance (Dubeux et al., 2016). Planting and growing these forage crops can involve considerable expense and is somewhat risky because rainfall is often unpredictable during the fall establishment period. The species and varieties for potential use vary in the distribution of production during the cooler months and in the type of soils where they are best adapted. This publication provides the most up-to-date information on current adapted cool-season forage varieties. The recommendation of varieties is based on multi-location, multi-year cultivar evaluation experiments that may include trials in Georgia and other states.